Iliopsoas Abscess Heralding the Diagnosis of Crohn’s Disease in a Young Male - Majed Ali; Karam Karam; Emanuel-Youssef Dib; Lamia Azizi; Elias Fiani (Case Reports in Medicine)
Iliopsoas abscess (IPA) is a rare but potentially life-threatening complication that may occur in patients with Crohn’s disease. We present the case of a 28-year-old male with Crohn’s disease who developed a complicated IPA. Diagnosis was confirmed via CT imaging and colonoscopy, revealing a fistulous connection to the terminal ileum. The treatment involved percutaneous drainage (PCD), antibiotics, and infliximab. Timely diagnosis, appropriate imaging, and multidisciplinary care are critical to prevent morbidity and recurrence in patients with Crohn’s disease complicated by IPA. This case highlights the importance of personalized treatment strategies and close follow-up in managing Crohn’s-related IPA.